Hilfer-Hadamard Nonlocal Integro-Multipoint Fractional Boundary Value Problems. (17th December 2021) - Promsakon, Chanon; Ntouyas, Sotiris K.; Tariboon, Jessada
Abstract : This paper is concerned with the existence and uniqueness of solutions for a new class of boundary value problems, consisting by Hilfer-Hadamard fractional differential equations, supplemented with nonlocal integro-multipoint boundary conditions. The existence of a unique solution is obtained via Banach contraction mapping principle, while the existence results are established by applying Schaefer and Krasnoselskii fixed point theorems as well as Leray-Schauder nonlinear alternative. Examples illustrating the main results are also constructed.